Hubungan pola komunikasi dengan perilaku seksual berisiko pada remaja : Hubungan Pola Komunikasi dengan Perilaku Seksual Berisiko pada Remaja - Reza Fajar Amalia; Amalia, Reza Fajar; Nadhifa, Dhiya Sary (Jurnal Kesehatan Masa Depan, 2024)
Background: Risky sexual behavior among teenagers is increasingly common. Risky sexual behavior is sexual behavior that has a negative impact on health. Parental communication patterns are related to risky sexual behavior in adolescents. Good communication has a positive impact on teenagers' openness to their parents. Communication between parents and teenagers is known to play a role in preventing risky sexual behavior in teenagers.Purpose: This study aims to identify and synthesize scientific evidence regarding the relationship between communication patterns and risky sexual behavior in adolescents. Methods: This study uses a literature review design with the Google Scholar and Pubmed databases. The inclusion criteria have titles and content relevant to the objectives, the year of publication is 2018–2023, and they use Indonesian and English. Meanwhile, the exclusion criteria were incomplete article structure. Results: The results of a literature review show that there is a relationship between communication patterns and risky sexual behavior in adolescents. Adolescents who have functional communication and sexual communication with their parents are shown to have a low chance of experiencing risky sexual behavior. In addition, this communication can be influenced by gender, parents' education, girlfriend ownership, number of family members, school location, the father's level of maturity, the mother's openness to reproductive health issues, communication attitude, awareness of the need for reproductive health information, and accessibility of health information.